ANALYSIS OF 4-HYDROXYCYCLOPHOSPHAMIDE IN CANCER PATIENTS PLASMA FOR THERAPEUTIC DRUG MONITORING OF CYCLOPHOSPHAMIDE - Harahap, Yahdiana; Samuel, Christian; Andalusia, Rizka; Syafhan, Nadia Farhanah (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: To quantify 4-hydroxycyclophosphamide in cancer patients' plasma for therapeutic drug monitoring of cyclophosphamide. Methods: The blood was collected at 0.5 and 1 h after administration of chemotherapy. Prior to analysis, 4-OHCP in plasma was derivatized with semicarbazide HCl, then was extracted using 4 ml ethyl acetate and finally was determined by Ultra High-Performance Liquid Chromatography–tandem mass spectrometry. Chromatographic separation was conducted using waters acquity BEH C18 column (1.7 μm; 50 mm x 2.1 mm). The mobile phase consisted of formic acid 0.1% and methanol (50: 50, v/v), column temperature 30 °C and flow rate of 0.3 ml/min. Mass detection was performed on waters xevo TQD equipped with an electrospray ionization (ESI) source at positive ion mode in the multiple reaction monitoring (MRM). Cyclophosphamide was detected at m/z 260.968>139.978, 4-hydroxycyclophosphamide-semicarbazide at m/z 338.011>224.97, and hexamethylphosphoramide as internal standard at m/z 180.17>92.08. Results: The method was linear in the range of 5–1000 ng/ml for cyclophosphamide and also for 4-hydroxycyclophosphamide. The results showed that the level of 4-OHCP in 39 cancer patients was in the range of 5.02 ng/ml to 832.44 ng/ml. Conclusion: 4-hydroxycyclophosphamide was detected on 39 patient samples with the lowest level of 5.40ng/ml and the highest level was 832.44 ng/ml. This can be a parameter that the regiment of cyclophosphamide was effective.